Persistence of Immune Responses Through 36 Months in Healthy Adults After Vaccination With a Novel Staphylococcus aureus 4-Antigen Vaccine (SA4Ag). (24th December 2019) - Creech, C Buddy; Frenck, Robert W; Fiquet, Anne; Feldman, Robert; Kankam, Martin K; Pathirana, Sudam; Baber, James; Radley, David; Cooper, David; Eiden, Joseph; Gruber, William C; Jansen, Kathrin U; et al.
Abstract: Background: Staphylococcus aureus causes serious health care– and community-associated disease, requiring improved preventive measures such as vaccines. The investigational S. aureus 4-antigen vaccine (SA4Ag), comprising capsular polysaccharide serotypes 5 and 8 (CP5 and CP8) conjugated to CRM197, recombinant mutant clumping factor A (r m ClfA), and recombinant manganese transporter protein C (rP305A or rMntC), was well tolerated, inducing robust functional immune responses to all 4 antigens through 12 months postvaccination. This is a serological extension study through 36 months postvaccination. Methods: In 2 previous studies, healthy adults received SA4Ag, SA3Ag (without rMntC), or placebo; serology was also assessed at 24 and 36 months postvaccination. Functional immune responses (antibody responses that facilitate killing of S. aureus or neutralize S. aureus virulence mechanisms) were assessed with opsonophagocytic activity killing assays (CP5 or CP8) and a fibrinogen-binding inhibition assay (ClfA). A competitive Luminex immunoassay assessed ClfA and rMntC responses. Adverse events within 48 hours of blood draw were recorded. Results: Four hundred forty subjects (18–64 years old, 255; 65–85 years old, 185) were enrolled. At 24 and 36 months postvaccination, subjects receiving SA4Ag had substantially higher geometric mean titers (GMTs) for CP5, CP8, and ClfA vs baseline; geometric mean fold rises (GMFRs) from baseline to month 36 were 2.7–8.1. For rMntC, 36-month GMTs declined from peak levels but remained above baseline for all SA4Ag groups; GMFRs from baseline to month 36 were 1.8 and 1.5 in the younger and older cohorts, respectively. Conclusions: Persistent functional immune responses to S. aureus antigens were observed through 36 months in healthy adults. ClinicalTrials.gov: NCT01643941 and NCT01364571.